MASA IDDAH WANITA KARIR YANG DI TINGGAL MATI SUAMI ENURUT IMAM SYAFI’I DAN KOMPILASI HUKUM ISLAM - Rifki Zaenul Fawwas; ibnu Jazari; Ahmad Subekti (Jurnal Hikmatina, 2022)
Women as citizens and human resources have the same rights and obligations as well as opportunities with men to play a role in development in all fields. The role of women as equal partners to men is realized through increasing the independence of their active role in development, including efforts to create a family of faith and piety, healthy, as well as for the development of children, youth and youth. In this study, the authors use library research, namely research conducted by reviewing or reviewing library sources. The type of research from this study is a text study, namely examining texts in the form of scientific works with the title Kitabul Fathul Qarib Fathul Mu'in Safinatun Najah and various other sources of study, either in the form of classic books by scholars. The results of the research of the Imam Syafi'i madzab agreed that the iddah obligation had been divorced by her husband or because of the husband's death. The period of iddah that is left for her husband to die is to wait for 4 months and 10 days if she is not pregnant, and a career woman who is a follower of Imam Syafi'i which basically is not allowed to leave the house, but if there is an excuse, she can leave the house